Intra‐bolus pressure and esophagogastric gradient, assessed with high‐resolution manometry, are associated with acid exposure and proximal migration of refluxate. Issue 8 (6th November 2015) - Ribolsi, M.; Balestrieri, P.; Holloway, R. H; Emerenziani, S.; Cicala, M.
Summary: Trans‐sphincteric pressure gradient (TSPG) seems to play a relevant role in eliciting refluxes during transient lower esophageal sphincter relaxations (TLESRs). Intra‐bolus pressure (IBP) is considered to be correlated to esophageal wall tone. We aimed to evaluate the relationship between IBP, TSPG during TLESRs and the dynamic properties of refluxate in gastroesophageal reflux disease. Sixteen non‐erosive reflux disease (NERD), 10 erosive disease (ERD) patients and 12 healthy volunteers (HVs), underwent 24‐hour impedance‐pH monitoring and combined high‐resolution manometry‐impedance before and 60 minutes. After a meal, ERD patients presented a significantly lower mean IBP (4.7 ± 1.6 mmHg) respect to NERD patients (8.9 ± 2.8 mmHg) and HVs (9.2 ± 3.2 mmHg). NERD patients with physiological abnormal acid exposure time showed a mean IBP (10.4 ± 3.1 mmHg) significantly higher than that in NERD with pathological abnormal acid exposure time (5.1 ± 1.5 mmHg). The TSPG value was significantly higher during TLESRs accompanied by reflux than during TLESRs not associated with reflux, both in patients and in HVs. A significant direct correlation was found between IBP, TSPG and proximal spread of refluxes in patients and in HVs. Gastroesophageal reflux disease patients display different degrees of esophageal distension. An increased compliance of the distal esophagus may accommodate larger volumes of refluxate and likely facilitates the injuries development. Higher TSPG values appear to facilitate the occurrence of refluxes during TLESRs. In patients with NERD, higher TSPG and IBP values favor proximal spread of refluxate and hence may play a relevant role in symptom generation.